BIODIVERSITY AND ITS USE AT TAUNSA BARRAGE WILDLIFE SANCTUARY, PAKISTAN - F. Bibi; Z. Ali; S. N. Qaisrani; S. Y. Shelly; S. Andleeb (Journal of Animal and Plant Sciences, 2013)
This study determined the livelihood conditions of the peoples of three villages (Bait Qaimwala, Basti Allahwali and Jannu) and their dependency on biodiversity of Taunsa Barrage Wildlife Sanctuary, Pakistan from 2009 to 2011. For socio-economic status, Participatory Human Resource Interaction Appraisal method was used and for biodiversity assessment, direct census method and point count were used. Floral biodiversity contained 79 species of plants including; trees (n꞊48 species); herbs (n꞊8 species); shrubs (n꞊9 species); grasses (n꞊7 species); reeds (n꞊5 species) and weeds (n꞊2 species).Fauna included fish (n=21 species), amphibians (n=3 species), reptiles (n=9 species), mammals (n=14 species) and birds (n=171) species. The high illiteracy rate (64 percent) in the surroundings of TBWS was estimated. Overall the local community was dependent on wetland products for use of fuel wood (77 percent), livestock grazing (100 percent), fishing (90 percent), hunting, freshwater turtles trading (10 percent) and others (9 percent). Villagers who live in mud-built houses constitute 42 percent, concrete houses 30 percent and thatched houses 28 percent. Typical means of transportation in the area was still animal driven cart (25 percent). In Bait Qaimwala 75 percent households were ultra poor. In Basti Allahwali 15 percent households were poor, 35 percent extremely poor and 5 percent ultra poor. In Jannu village, 55 percent households were poor and 45 percent were non poor. There is need to reorganize the social sector and help local communities to fully benefit from the potential of ecotourism. In conclusion, community participation for sustainable use of natural resources in wildlife sanctuary will give a new strength to biodiversity conservation in study area.
Keywords: socioeconomic; biodiversity; local communities; resource use; Taunsa Barrage Wildlife Sanctuary